Transcriptomic and Metabolomic Analyses Reveal Inhibition of Hepatic Adipogenesis and Fat Catabolism in Yak for Adaptation to Forage Shortage During Cold Season - Zheng, Juanshan; Du, Mei; Zhang, Jianbo; Liang, Zeyi; Ahmad, Anum Ali; Shen, Jiahao; Salekdeh, Ghasem Hosseini; Ding, Xuezhi (Frontiers in Cell and Developmental Biology, 2022)
Animals have adapted behavioral and physiological strategies to conserve energy during periods of adverse conditions. Hepatic glucose is one such adaptation used by grazing animals. While large vertebrates have been shown to have feed utilization and deposition of nutrients—fluctuations in metabolic rate—little is known about the regulating mechanism that controls hepatic metabolism in yaks under grazing conditions in the cold season. Hence, the objective of this research was to integrate transcriptomic and metabolomic data to better understand how the hepatic responds to chronic nutrient stress. Our analyses indicated that the blood parameters related to energy metabolism (glucose, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, lipoprotein lipase, insulin, and insulin-like growth factor 1) were significantly (P < 0.05) lower in the cold season. The RNA-Seq results showed that malnutrition inhibited lipid synthesis (particularly fatty acid, cholesterol, and steroid synthesis), fatty acid oxidation, lipid catabolism and promoted gluconeogenesis by inhibiting the PPAR and PI3K-Akt signaling pathways. For metabolite profiles, 359 metabolites were significantly altered in two groups. Interestingly, the cold season group remarkably decreased glutathione and PC (18:2(2E, 4E)/0:0). Moreover, integrative analysis of the transcriptome and metabolome demonstrated that glycolysis or gluconeogenesis, PPAR signaling pathway, fatty acid biosynthesis, steroid biosynthesis, and glutathione metabolism play an important role in the potential relationship between different expression genes and metabolites. The reduced lipid synthesis, fatty acid oxidation, and fat catabolism facilitated gluconeogenesis by inhibiting the PPAR and PI3K-Akt signaling pathways to maintain the energy homeostasis of the whole body in the yak, thereby coping with the shortage of forages and adapting to the extreme environment of the Qinghai-Tibetan Plateau (QTP).